Internalisasi Ajaran Agama Hindu Dalam Pendidikan Karakter di SMPN 7 Singaraja - Putu Sanjaya; Wayan Juliana (Cetta: Jurnal Ilmu Pendidikan, 2023)
Educating students to become people of noble character is the responsibility of every school. Hindu religious teachings have become part of character education. In Hinduism, there are many teachings that can be internalized by students so that they form a character that is in accordance with the values and teachings of Hinduism. Student character that is in harmony with the teachings of Hinduism is the basis for realizing the noble character of the nation's next generation. This research uses qualitative methods with a descriptive analysis approach. Through the methods used, the teachings of Hinduism that are internalized into character education include Panganjali, Yadnya, events, Tri Kaya Parisudha, Catur Paramitha, Tri Hita Karana, and also stories taken from the Mahabharata. In the character education process, Hindu religious teachings related to character education values found in the learning process are part of the 18 existing character values. At SMPN 7 Singaraja, the values of Hindu religious teachings in character education are implemented when carrying out learning in class. The values of Hindu religious teachings in the learning process also reflect character education which includes 7 of the 18-character values according to the Ministry of National Education. Hindu religious values in character education include 9-character values, namely, religiousness, tolerance, discipline, hard work, independence, curiosity, caring for the environment, friendly/communicative and responsibility. These values are found in Hindu religious lesson materials or in learning activities.